(untitled) (Jurnal Penelitian Kehutanan Wallacea, 2019)
Air pollution is still a serious problem, especially in big cities in Indonesia. One of the heavy metals that is the source of air pollutant and is very harmful to health and the environment is lead (Pb). Mitigation form that can be done for handling lead air pollution is through tree planting. Therefore, it is important to study the appropriate plant species to be recommended for absorbing lead in the air. This study aims to determine the concentration of lead on the leaves of trees around the Kadu Manis Industrial Region, Tangerang. Measurements of lead concentration were carried out using the 3030-H-APHA (American Public Health Association) modification method in 2012 and Working Instructions (IK) metal 01 of 2014. Based on the analysis, there are 5 (five) species which are recommended to be used as the lead absorber: Pinus (Pinus merkusii), Beringin (Ficus benjamina), Kemuning (Murraya paniculata), Flamboyan (Delonix regia), and Bintaro (Cerbera manghas). The lead concentration found on the leaves of these tree species was 770.8 ppm, 440.6 ppm, 229.0 ppm, 168.1 ppm, and 152.1 ppm for pine, beringin, kemuning, flamboyan, and bintaro, respectively. Planting tree species that has the ability to adsorb high lead is one form of mitigation of heavy metal pollution of lead in the air, especially in the industrial region.